Chinese herbal medicine for the treatment of children with cerebral palsy: a meta-analysis of randomized controlled trials with core herbs exploration - Huang, Ying-Yu; Cheng, Ya-Yun; Chen, Hsing-Yu; Fu, Ren-Huei; Chang, Yi-Jung; Yang, Tsung-Hsien (Frontiers in Pharmacology, 2025)
IntroductionChinese herbal medicine (CHM) taken orally is frequently utilized to enhance functional ability and independence in cerebral palsy (CP); nonetheless, there is a lack of current evidence regarding the efficacy of oral CHM in treating CP. Additionally, the general complexities of CHM prescriptions often obscure the underlying mechanisms. Our study aims to assess the efficacy of oral CHM in treating CP, a meta-analysis will be conducted on randomized clinical trials (RCTs).Materials and methodsWe searched Cochrane Library, PubMed, Embase, Scopus, PubMed Central, ClinicalTrials.gov, and China National Knowledge Infrastructure (CNKI), from 1990 to 2022. The primary outcome was the improvement in Effectiveness rate (ER). The secondary outcome was the improvement of motor function (GMFM). Subgroup analysis and trial sequential analysis (TSA) were conducted to confirm results consistency. Core CHMs were investigated through system pharmacology analysis.ResultsSeventeen RCTs were analyzed, in which CHMs with Standard treatment (ST) were compared to ST alone. All participants were aged <11 years. More participants in the CHM group achieved prominent improvement in ER (RR: 1.21, 95% CI: 1.13–1.30, p-value < 0.001, I2 = 32%) and higher GMFM improvement (SMD: 1.49; 95% CI: 1.33–1.65, p-value < 0.001, I2 = 92%). TSA also showed similar results with proper statistical power. Core CHMs, such as Glycyrrhiza uralensis Fisch. Ex DC., Poria cocos (Schw.) Wolf, Paeonia lactiflora Pall., processed Rehmannia glutinosa (Gaertn.) DC., Astragalus mongholicus Bunge, and Angelica sinensis (Oliv.) Diels, exerted effects on immune modulation and metabolism systems. The subgroup analysis showed participants using core CHMs or longer CHM treatment duration, and studies enrolling CP with spastic or mixed type, or mild-to-moderate severity had better outcomes in CHM groups with less heterogeneity.ConclusionCHMs may have a positive impact on managing pediatric CP; however, the potential bias in study design should be improved.Systematic Review RegistrationIdentifier CRD42023424754.